2019
DOI: 10.5194/acp-19-8311-2019
|View full text |Cite
|
Sign up to set email alerts
|

Unusual chlorine partitioning in the 2015/16 Arctic winter lowermost stratosphere: observations and simulations

Abstract: Abstract. The Arctic winter 2015/16 was characterized by cold stratospheric temperatures. Here we present a comprehensive view of the temporal evolution of chlorine in the lowermost stratosphere over the course of the studied winter. We utilize two-dimensional vertical cross sections of ozone (O3) and chlorine nitrate (ClONO2), measured by the airborne limb imager GLORIA (Gimballed Limb Observer for Radiance Imaging of the Atmosphere) during the POLSTRACC/GW-LCYCLE II/GWEX/SALSA campaigns, to investigate the t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 95 publications
(129 reference statements)
3
22
0
Order By: Relevance
“…GLORIA measurements during flight PGS-08 on 20 January 2016, spatially close to Ny-Ålesund show on average an agreement with the profile measured by the ozone sonde within 25 ppbv, even in the upper troposphere. This comparison extends the finding of Johansson et al (2018), who found GLORIA O 3 retrievals to agree with FAIRO in situ O 3 measurements within the estimated errors of the instruments. Ozone measurements above the aircraft were possible with the WALES instrument during flight PGS-05 on 21 December 2015.…”
Section: Synergy Between In Situ and Remote Sensing Instruments And Csupporting
confidence: 88%
See 4 more Smart Citations
“…GLORIA measurements during flight PGS-08 on 20 January 2016, spatially close to Ny-Ålesund show on average an agreement with the profile measured by the ozone sonde within 25 ppbv, even in the upper troposphere. This comparison extends the finding of Johansson et al (2018), who found GLORIA O 3 retrievals to agree with FAIRO in situ O 3 measurements within the estimated errors of the instruments. Ozone measurements above the aircraft were possible with the WALES instrument during flight PGS-05 on 21 December 2015.…”
Section: Synergy Between In Situ and Remote Sensing Instruments And Csupporting
confidence: 88%
“…High-resolution ECMWF forecasts, together with chemistry transport modeling from the CLaMS model and the Mission Support System (MSS) flight planning tool (Rautenhaus et al 2012) and satellite data from MLS and CALIPSO, were of great value in flight planning. The excellent agreement between the GLORIA infrared remote sensing data with in situ observations (Johansson et al 2018) enabled us to extend the findings sampled in situ at flight altitude throughout the lowermost stratosphere and sometimes even across the tropopause into the Arctic upper troposphere. An impressive demonstration of these capabilities has been provided for a case study of a tropopause folding event and assessment of the quality of ECMWF meteorological forecasts (Woiwode et al 2018).…”
Section: Discussionmentioning
confidence: 62%
See 3 more Smart Citations